First Decade of the National Cancer Institute's Affordable Cancer Technologies Program: Accelerating Translational Technology Research and Development for Cancer Globally - Paul C. Pearlman; Rao Divi; Rebecca Huppi; Elise Garton; Srivatsan Kidambi; Pushpa Tandon; Miguel Ossandon; Ophira Ginsburg; Satish Gopal (JCO Global Oncology)
Since 2014, the National Cancer Institute Affordable Cancer Technologies (ACTs) program has supported a broad research portfolio focused on the development and validation of new technologies for global cancer control. ACTs projects are conducted by international teams composed of investigators from the United States and low- and middle-income countries, spurring important contextually relevant innovations. During its first decade, the ACTs program ushered in new technology platforms, led to commercialized products, and affected health policies and programs worldwide including in the United States. It has allowed a new generation of investigators working across disciplines and national borders to pursue novel technological solutions and leverage new analytic methods to advance human health. This commentary lays out the scope and accomplishments of the ACTs program to date while considering possible future research directions.